Metacognitive group training for schizophrenia spectrum patients with delusions: a randomized controlled trial. Issue 14 (October 2014) - van Oosterhout, B.; Krabbendam, L.; de Boer, K.; Ferwerda, J.; van der Helm, M.; Stant, A. D.; van der Gaag, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Metacognitive training (MCT) for patients with psychosis is a psychological group intervention that aims to educate patients about common cognitive biases underlying delusion formation and maintenance, and to highlight their negative consequences in daily functioning. Method In this randomized controlled trial, 154 schizophrenia spectrum patients with delusions were randomly assigned to either MCT + treatment as usual (TAU) or TAU alone. Both groups were assessed at baseline, and again after 8 and 24 weeks. The trial was completed fully by 111 patients. Efficacy was measured with the Psychotic Symptom Rating Scales (PSYRATS) Delusions Rating Scale (DRS), and with specific secondary measures referring to persecutory ideas and ideas of social reference (the Green Paranoid Thoughts Scale, GPTS), cognitive insight (the Beck Cognitive Insight Scale, BCIS), subjective experiences of cognitive biases (the Davos Assessment of Cognitive Biases Scale, DACOBS) and metacognitive beliefs (the 30-item Metacognitions Questionnaire, MCQ-30). Economic analysis focused on the balance between societal costs and health outcomes (quality-adjusted life years, QALYs). Results Both conditions showed a decrease of delusions. MCT was not more efficacious in terms of reducing delusions, nor did it change subjective paranoid thinking and ideas of social reference, cognitive insight or subjective experience of cognitive biases and metacognitive beliefs. The results of the economic analysis were not in favour of MCT + TAU. Conclusions In the present study, MCT did not affect delusion scores and self-reported cognitive insight, or subjective experience of cognitive biases and metacognitive beliefs. MCT was not cost-effective.